Parental Knowledge and Practices Associated with Dental Caries among Children with Thalassemia Aged 6–12 Years Attending the Children’s Hospital, Vientiane Capital, Lao PDR - THAMMAVONGSA, Viengsay; PHENTHAVONG, Manevone; INTHAKOUN, Viengsavanh; THAMMAVONGSA, Pouthasone; HOMSAVANH, Amphayvanh; THAMMAVONGSA, Khambay; THONGTERM, Vimonh (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The aims of this study were to investigate the situation of parents who took their children to receive dental caries services related to thalassemia, to assess parents’ knowledge and practices regarding dental caries in children with thalassemia, and to examine the relationship between parental knowledge and dental caries among children with thalassemia. The sample consisted of 375 parents and 375 children. Data were analyzed using the STATA program version 13 to calculate percentages, and associated P value < 0,05. The results showed that most parents were female and aged between 31 and 45 years. More than 90% belonged to the Lao Loum ethnic group. Approximately 60% of families had a monthly income of more than 1,500,000 kip. Most children were aged 6–8 years, and more than 68% had dental caries associated with thalassemia. Most parents demonstrated good understanding of dental caries related to thalassemia and were able to answer questions accurately regarding the condition. The study also found that thalassemia affected dental decay in 86.9% of permanent teeth and 92.8% of primary (milk) teeth. Factors significantly associated with child oral health included the 9–12-year age group with p < 0.001), parental oral health care practices for children with p = 0.008). The proportion of children aged 6–12 years with thalassemia and dental caries was high for both permanent and primary teeth. These findings highlight the importance of developing oral health care plans and preventive oral health programs for children with thalassemia admitted to hospitals.